A Feasibility study on Speltix Electronix, Inc. Printed circuit boards - Alcasabas, Ramon Manolo A.; Cariaga, Vincent Paul Y.; Eiaw, Sherilyn U.; Irong, Elton Cris E.; Uy, Ofelia E. (College of Engineering, 1999)
A printed circuit board (PCB) is an electric circuit that replace individual wire lead connections with the use of two-dimensional metallic conductive patterns bonded to one or more dielectric substrates. It is used in almost any electronic product due to the need of interconnecting electronic components. It is the most commonly used platform for manufacturing electronic systems. Due to its custom-designed attitude, it is very often the most expensive single component of any electronic equipment. The market study conducted showed a substantial market for PCBs in the Philippines. However, there exists an unsatisfied demand of 22,917,595 square feet of PCB on the year 1999. In addition, most of the demand of PCBs in the Philippines was satisfied by foreign PCB manufacturers. Hence, Speltix Electronix aims to lessen PCB importation by establishing its presence in the local market. THe company aims to have a 3.1815% target market share in its first year and grow by 2% per annum subsequently. The steady growth in the target market comprising of communications and computer sectors gives the Company enough confidence to attain these market shares. The technical study conducted also came up with favorable results. Speltix Electronix will use only one continuous production line in PCB manufacturing. The machinery and equipment to be used will be imported and will cost the company Php 21,725,099. All of the raw materials to be used, except the FR-4 copper clad laminate, will be purchased in the local market. The FR-4 copper clad laminate will be imported from Hong Kong. The plant will be located on a 5000 square meter land in the New Cavite Industrial City. Aside from the proximity to its prospective customers, the site has amenities suitable for PCB production. In addition, the people living in the area can make-up the direct labor workforce of the Company. All in all, Php 248,193,169.30 was estimated to venture into the manufacture of PCBs in the Philippines. The organization and management study showed a corporate form of ownership will be established for Speltix Electronix due to the benefits of being such an entity. Some of the benefits include pooling of initial capital, attraction of loan financing and additional capital, and motivation of the corporation's employees. On the first three years of operation, 57 workers will comprise the workforce of the company. On the fourth and firth year of operation, the number will increase to 82. The employees will enjoy benefits such as 13th month pay, SSS, PAG-IBIG, Medicare, and employee's compensation. The capital intensiveness of venture on Speltix Electronix would require the stability and capital support of being established as a corporation. The project will be financed by Metrobank on a 40:60 debt-to-equity ratio. Hence, Php 99,277,267.72 will be loaned by the Company while the remaining PhP 148,915,901.58 will be financed through the issuance of stock at Php 100.00 per share. The financial study showed a net income of PhP 177,451,462.65 will be projected on the first year. The projected increasing assets of PhP 453,804,704.77 to PhP 1,077,716,516.96 during the first five years of operation show a strong financial position for Speltix Electronix. Financial tests yielded positive results. A two-year payback period coupled with 439.63% average rate of return makes the investment on the project an attractive venture. The sensitivity analysis shows the Net Present Value and the Internal Rate of Return to be PhP 114,143,649.82 and 80.35% respectively. These further prove the profitability of the project considering a 30% minimum attractive rate of return was set to evaluate the results. The social profitability study further proved the feasibility of Speltix Electronix. Venturing into the business gives benefits to the local community, local market, and government . The local community will have increased technical standards, and employment that improves the standard of living of the community. The local market will gain from the venture through product innovation, the possibility of influencing prices and strategies, and the purchase of local materials. Lastly, corporate income tax, revenue from withholding tax, municipal tax, and importation tax generated from the Company will give additional revenues to the government. Thus ,the venture on the manufacture of PCBs in the Philippines is not only financially attractive but is also attractive due to its social and economic contributions. The results of the in-depth analysis of Speltix Electronix have proved the venture on the manufacture of printed circuit boards in the Philippines to be highly feasible one.